Hybrid Method Neighbor Node Discovery in Wireless Sensor Networks: A Framework - Mekala, Sagar; Kaila, Shahu Chatrapati; Matang, Jyothi Rani (UI Scholars Hub, 2024)
Wireless devices are now being adapted for diverse purposes, such as healthcare, agriculture, transportation, and tactical operations, which present challenges in network formation owing to high device mobility. Current methods rely on discovery techniques for forming wireless sensor networks (WSNs); however, the existing research has been criticized for its high time complexity and redundant neighbor discovery process. In this study, we provide a hybrid strategy to effectively handle the difficulties of locating neighboring nodes in WSNs. Our method combines several strategies to produce precise and effective neighbor detection. Herein, shared memory–based discovery, a beacon technique, and range and distance overlap detection comprise three main phases of the hybrid approach. This approach improves time complexity by 50% and reduces redundant node discovery by nearly 30%.